1982
DOI: 10.1029/jc087ic09p07273
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric injections of nuclear debris: Strontium 89 and 90 from Chinese weapons tests

Abstract: The concentrations of 89Sr and 90Sr in a total of 455 samples of individual rain and snow collected at Fayetteville (36°N, 94°W), Arkansas, were determined radiochemically during the period between April 1973 and June 1981. Nine atmospheric nuclear tests were conducted by the government of China at Lop Nor (40°N, 90°W) during the period 1973–1981. The Chinese nuclear tests of June 27, 1973 (3‐megaton, the 15th test); June 17, 1974 (1–2 megaton, the 16th); January 23, 1976 (reported to have been a low‐yield dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…The amount of excess concentration of 210Po in air varies seasonally 210Po obtained was then compared with the and from one geographical location to another total amount of 90Sr released by the 16 October in a very complicated manner; and (c) there 1980 Chinese nuclear explosion of a 0.2 to 1 are a number of sources other than the vol megaton device, which was similarly obtained canoes which may contribute to the production from the analyses of the concentrations of 90Sr of excess 210Po in the atmosphere. For example, in the entire series of individual rain and snow Turekian et al (1974) reported that an excess samples (Kuroda et al, 1984;Burchfield et of 210Po over 210Pb is produced by plankton in al., 1983;Burchfield et al, 1982). the seas and is then transported from the surface The results obtained by Kuroda et alL waters to the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…The amount of excess concentration of 210Po in air varies seasonally 210Po obtained was then compared with the and from one geographical location to another total amount of 90Sr released by the 16 October in a very complicated manner; and (c) there 1980 Chinese nuclear explosion of a 0.2 to 1 are a number of sources other than the vol megaton device, which was similarly obtained canoes which may contribute to the production from the analyses of the concentrations of 90Sr of excess 210Po in the atmosphere. For example, in the entire series of individual rain and snow Turekian et al (1974) reported that an excess samples (Kuroda et al, 1984;Burchfield et of 210Po over 210Pb is produced by plankton in al., 1983;Burchfield et al, 1982). the seas and is then transported from the surface The results obtained by Kuroda et alL waters to the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…It is worthy of note here, however, that Turekian et al (1983) have recently reported the values of 17.1 (dpm/cm2/y) at Bermuda (33'N) and 22.7 (dpm/cm2/y) at New Haven (41°N), Connecticut. The 90 Sr and 210Po data were taken from the reports of Burchfield et al (1982), Burchfield and Kuroda (1983), and Kuroda et al (1984). A marked increase in the 90 Sr/' Be ratio in rain observed during the first half of 1981 is attributable to the 25th Chinese nuclear explosion of 16 October 1980 (Burchfield et al, 1982;Burchfield and Kuroda, 1983).…”
mentioning
confidence: 99%
“…The 90 Sr and 210Po data were taken from the reports of Burchfield et al (1982), Burchfield and Kuroda (1983), and Kuroda et al (1984). A marked increase in the 90 Sr/' Be ratio in rain observed during the first half of 1981 is attributable to the 25th Chinese nuclear explosion of 16 October 1980 (Burchfield et al, 1982;Burchfield and Kuroda, 1983). Note that the South African incident of 22 September 1979, in which a small nuclear weapon was reported to have been tested in the southern hemisphere, had no significant effect on the 90 Sr concentrations in rain collected at Fayetteville, Arkansas.…”
mentioning
confidence: 99%
“…The amount of excess 210Po obtained was then compared with the total amount of 90 Sr released by the 16 October 1980 Chinese nuclear explosion of a 0.2 to 1 megaton nuclear device (BURCHFIELD et al, 1982, BURCHFIELD andKURODA, 1983), which was similarly obtained from the analyses of the concentrations of 90 Sr in the entire series of rain and snow samples.…”
Section: Methodsmentioning
confidence: 99%